Hypertension Among Yoga Practitioners: A Cross-Sectional Study at I Gusti Bagus Sugriwa State Hindu University, Denpasar - Pratama, Wirawan Tantra; Putra, I Putu Yudi Pramana; Juhanna, Indira Vidiari (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction: Hypertension, or high blood pressure, can lead to severe illnesses and death. Yoga has been identified as a method to lower blood pressure by improving blood circulation and heart function. This study evaluates the benefits of yoga in managing hypertension and identifies contributing factors. Methods: An analytical observational method with a cross-sectional approach was used. The study included 103 yoga practitioners selected via probability sampling. Blood pressure was measured using digital and aneroid sphygmomanometers. Dependent variables included body mass index (BMI), age, and physical activity measured through the IPAQ questionnaire. Results : Yoga practitioners aged 18-39, predominantly females without a family history of hypertension and with normal BMI and high physical activity levels, generally had normal blood pressure. Fewer hypertension cases were observed in these groups. Those without a family history of hypertension had fewer cases compared to those with a history. Respondents with normal BMI mostly had normal blood pressure, but slight increases in hypertension were noted among overweight and obese individuals. No clear pattern was observed between coffee consumption and blood pressure. High physical activity levels were associated with normal blood pressure. Conclusion: Age, gender, family history, BMI, coffee intake, physical activity, smoking, and medication adherence impact grade 1 hypertension. Yoga effectively lowers blood pressure and manages stress. Integrating yoga into educational hypertension programs can enhance public awareness and management skills. Promoting yoga as part of a healthy lifestyle could significantly reduce hypertension prevalence and its societal health burden, fostering healthier communities resilient against hypertension risks.   Keywords: overview, hypertension, yoga